2023
DOI: 10.3390/plants12203520
|View full text |Cite
|
Sign up to set email alerts
|

Salinity Stress Tolerance in Plants

Libia Iris Trejo-Téllez

Abstract: Soil salinization negatively impacts plant development and induces land degradation, thus affecting biodiversity, water quality, crop production, farmers’ well-being, and the economic situation in the affected region. Plant germination, growth, and productivity are vital processes impaired by salinity stress; thus, it is considered a serious threat to agriculture. The extent to which a plant is affected by salinity depends mainly on the species, but other factors, including soil attributes, water, and climatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Seed germination, an important aspect in crop growth and development and a crucial factor in determining productivity, is severely affected by salt stress [35]. Strong salt tolerance in the germination stage lays a good foundation for later growth and development [36]. This study demonstrated a decreasing trend in the length and diameter of the hypocotyls, radicles, and dry and fresh weights of the shoots with increasing salt concentrations.…”
Section: Screening Of Peanut Salt Tolerancementioning
confidence: 60%
“…Seed germination, an important aspect in crop growth and development and a crucial factor in determining productivity, is severely affected by salt stress [35]. Strong salt tolerance in the germination stage lays a good foundation for later growth and development [36]. This study demonstrated a decreasing trend in the length and diameter of the hypocotyls, radicles, and dry and fresh weights of the shoots with increasing salt concentrations.…”
Section: Screening Of Peanut Salt Tolerancementioning
confidence: 60%